THE EFFECT OF COMPETENCY ON CIVIL SERVANTS PERFORMANCE IN THE HEALTH SERVICE OF PEKANBARU CITY - rupat, herman (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
In order to improve the quality and quantity of performance of Civil Servants (PNS) at the Pekanbaru City Health Office, it is necessary to conduct Competency research for all Civil Servants (PNS) of the Pekanbaru City Health Office. This competency is carried out so that office holders can occupy their positions in accordance with their educational qualifications, skills/ experience and attitudes. In general, the purpose of this study is to determine the effect of competence on employee performance at the Pekanbaru City Health Office. The number of samples in this study were 91 employees. In the overall validity test the statement of competence and performance variables are declared valid because the rcount > rtable (0.206) is obtained. Simple linear regression results obtained by the value of Y = 2.729 + 0.899X. From the partial test results or t test obtained value of tcount (6.928) > ttable (1.986) with a sig level of 0.000 < 0.05 which means that competence has a significant effect on performance. The coefficient of determination test results (R2) of 0.350 or 35 %, meaning that the magnitude of the influence or contribution given by the competency variable to the performance variable is 35 % while the remaining 65 % is influenced by other factors not examined in this study.